PRODUCTION OF PLANTING MATERIAL SALIX MATSUDANA KOIDZ. FOR PLANTATION GROWING IN THE CONDITIONS OF THE NORTH-EASTERN PART OF THE FOREST STEPPE OF UKRAINE - Мельник, Андрей; Токмань, Владимир (SWorldJournal, 2021)
Some elements of agricultural techniques for growing container planting material of Salix matsudana plants in closed and open ground of Sumy NAU are highlighted in the study.It is proposed to use seedlings with closed root system to create forest plantat